9x+4x+4+8=8x+3+4x

Simple and best practice solution for 9x+4x+4+8=8x+3+4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+4x+4+8=8x+3+4x equation:


Simplifying
9x + 4x + 4 + 8 = 8x + 3 + 4x

Reorder the terms:
4 + 8 + 9x + 4x = 8x + 3 + 4x

Combine like terms: 4 + 8 = 12
12 + 9x + 4x = 8x + 3 + 4x

Combine like terms: 9x + 4x = 13x
12 + 13x = 8x + 3 + 4x

Reorder the terms:
12 + 13x = 3 + 8x + 4x

Combine like terms: 8x + 4x = 12x
12 + 13x = 3 + 12x

Solving
12 + 13x = 3 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
12 + 13x + -12x = 3 + 12x + -12x

Combine like terms: 13x + -12x = 1x
12 + 1x = 3 + 12x + -12x

Combine like terms: 12x + -12x = 0
12 + 1x = 3 + 0
12 + 1x = 3

Add '-12' to each side of the equation.
12 + -12 + 1x = 3 + -12

Combine like terms: 12 + -12 = 0
0 + 1x = 3 + -12
1x = 3 + -12

Combine like terms: 3 + -12 = -9
1x = -9

Divide each side by '1'.
x = -9

Simplifying
x = -9

See similar equations:

| 2(16n+3)=-12 | | 10x+5(6)=0 | | (5x)(14x)+7=0 | | m(5-x)=2-y | | 3(x-5)=-12 | | a(c-5)+s(c-5)=0 | | g=3g+3u | | 20a^2-23ab+6b^2=0 | | 5(6z-1)-3(z+3)=11(z+1) | | 9x-(4x-5)-(-6x+1)= | | 22=0 | | 11x-77=0 | | 3x^2-25x+42=0 | | 275m^2+396n^2=0 | | 4y+112=180 | | x^2-x-48=16 | | 0.5(x-0.08)=0 | | x/3=3x-1 | | ln(x)+ln(8x)=-3 | | 5y+20=0 | | 5b+7b=60 | | s^2-12s+36= | | (x-2)/3=8 | | (x-2)/3-5=3 | | 4x^3+12x^2+10x+10=0 | | x-2/3-5=3 | | 2x+30+x= | | 24=-8(0.3p+9) | | 4(3x-2)=(6x+6) | | 4X+37+9X=180 | | X=45(16) | | 29x^2-7x=0 |

Equations solver categories